A way of supporting the servicing of production machines using reverse engineering and 3D printing techniques - Loska, Andrzej; Palka, Dorota; Bień, Alicja; Substelny, Katarzyna (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The use of machines and devices causes their components to wear out, which leads to damage. The easiest and fastest method of repair is to replace this element with a new one. The problem arises when the desired element is not available on the market, technical documentation is unavailable or the costs of acquiring a new element are too high. In such a situation, engineering reconstruction, also known as reverse engineering, is used, which allows for the reconstruction of technical documentation and the production of a new product thanks to additive technology. The article presents the process of reverse engineering and the types of additive manufacturing technology. The aim of the article is to present the possibilities of using the reverse engineering method and 3D printing in the reconstruction of sample machine parts. The work uses the FDM (Fused Deposition Modeling) spatial production technology. The relevance of the article is confirmed by the possibility of its practical use in the field of machine servicing support. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)